Standard flushing and sealing of venous indwelling catheter and related nursing management in a case of gangrene (1例脱疽患者静脉留置导管冲封管操作规范及护理) - ZHENG Jiaqi (郑佳琪); ZHI Hui (智慧) (Association of Integrative Nursing, 2021)
This paper reviewed the standard flushing and sealing of venous indwelling catheter and related nursing management in a patient with gangrene. According to the Infusion Therapy Standards of Practice, the catheter flushing and sealing operation was performed, and blood return and catheter blockage after catheter sealing were observed. Standard use of venous indwelling catheter can effectively reduce the risk of related complications, prolong the indwelling time of peripheral indwelling needle, and achieve the purpose of safe infusion. (本文回顾1例脱疽患者静脉留置导管冲封管操作规范及护理措施。护理人员严格遵守冲封管操作规范, 观察患者留置针封管后回血及导管堵塞情况。规范使用静脉留置导管冲封管, 对降低静脉留置导管相关并发症发生风险、延长外周留置针留置时间具有积极意义, 确保患者输液安全。)